The Core Values Method Within the Sufficiency Economy and Thai Societal Values - Whietley, Alma (HRD Journal, 2013)
This paper presents the core values method as a human resource development (HRD) initiative for the Thai context. In particular, the paper acknowledges the countermanding force of the sufficiency economy principle in combating the reported excesses of globalization and the capitalist ethic. A brief history of the development of job related training is presented, leading on to the change in discourse to human resource development. Thai business is interwoven with Buddhist values which are relational in nature, focusing on human qualities of graciousness and compassion. Writers on human resource development in Thailand support the values-driven approach to organizational development and within that, human resource development. The core values method (CVM) was designed for culture building and culture binding. A central feature of the CVM is of participation and ownership, recognising in particular, three stakeholding groups - managers, employees and customers. A step by step process is explained, beginning with values generation of each of the stakeholding groups and culminating in two confirming exercises. One is a mapping process such that organizational activities are mapped to organizational values and Thai values. From there, a matrix is produced such that values from the sufficiency economy principle, Thai values and organizational values are present across a range of organizational activities. Key Words : Human resource development, Thailand, Core values method